Responsible corporate change: detecting and managing employee stress. (28th March 2015) - McBride, D. I.; Lovelock, K.; Dirks, K. N.; Welch, D.; Shepherd, D.
Abstract: Background: All 120 health and safety inspectors employed by the New Zealand regulatory agency had their jobs disestablished during a restructuring process and were required to undergo an assessment process with tight time frames. Aims: To report on psychological morbidity during the transition to change. Methods: The Hospital Anxiety and Depression Scale (HADS) questionnaire was emailed to all 120 current inspectors to measure levels of anxiety (HAD-A) and depression (HAD-D). A score of <7 is in the normal range, scores of between 8 and 10 are suggestive of an anxiety (HADS-A) or mood (HADS-D) disorder and a score of >11 is indicative of a clinical disorder. Results: Replies were received from 36% (43) of the inspectors. Of the 40 usable responses, 47% (19) and 55% (22), respectively, had HAD-A and HAD-D scores greater than the case cut-off. Only 28% (11) and 15% (6), respectively, had scores that would be considered normal. Conclusions: The high scores evident in this sample are comparable to those found in patients with serious psychopathology. Change managers should recognize that the onus for primary prevention lies with the organization, in this case designing an assessment process that takes place over a reasonable time frame. They should also realize the requirement for the active monitoring of stress.